Design of an Evaluative Rubric for CT Integrated Curriculum in the Elementary Grades - Sullivan, Florence R.; Duan, Lian; Pektas , Emrah (CTE-STEM 2022 conference, 2022)
Despite the recent proliferation of research concerning integrating computational thinking (CT) into K-5th grade curriculum, there is little literature concerning how to evaluate the quality of CT integrated curricula, especially curricula integrating CT into language arts and social studies content areas. In this paper, we present a theoretically derived rubric for the evaluation of CT integrated curricula for grades K-5 across the curriculum (math, science, language arts, social studies). Our rubric is divided into two sections. The first section provides guidelines for identifying the integration type (disciplinary, multidisciplinary, interdisciplinary, or transdisciplinary). The second section presents six categories of evaluation that further subsume nine sub-categories. The principal categories of evaluation include the following: conceptual coherence, role of computational technology, assessment, use of multiple representations, play, and equity. We include the play category as an aspect of developmental appropriateness. Play is an important pedagogical approach for learning in the early grades. Our work takes place in the context of the Computer Science (CS) for All initiative in the United States which emphasizes the goal of improving racial and gender diversity in CS participation. Therefore, creating integrated lessons that address equity is important. Our paper describes rubric development from the theoretical perspectives that underlie the inclusion of each type, category, and sub-category. Our evaluative rubric can guide future efforts to integrate CT/CS into the elementary curricula. Researchers can utilize our rubric to evaluate and analyze CT-integrated curricula, and educators can benefit from using this rubric as a guideline for curriculum development.